MENGENAL UNDUR-UNDUR LAUT (CRUSTACEA: DECAPODA: HIPPIDAE) DAN MANFAATNYA BAGI KEHIDUPAN - Rianta Pratiwi (Pusat Penelitian Oseanografi LIPI, 2018)
GET CLOSER TO KNOW THE SEA MOLE CRAB (CRUSTACEA: DECAPODA: HIPPIDAE) AND THE BENEFITS FOR LIFE. The mole crab or also known as yutuk is an animal belonging to the group of crustaceans. The crab has a small body size and live immersed in the open beach sand in the tropics and sub-tropics. In Indonesia, many are found along the beaches around Yogjakarta, Central Java. One of the most common of species is Emerita emertus, Hippa adactyla and Hippa ovalis. It is highly hunted by the locals as the crab has high economic value, especially for source of nutrious food. Ecologically the crab is an important component in the food chain, in which the crab acts as an initial consumer in trophic level. Continuous and large-scale harvesting can disrupt the stability of the population in nature, therefore knowledgebased management is required to sustain the balanced population